2013
DOI: 10.1177/0956797613482467
|View full text |Cite
|
Sign up to set email alerts
|

Swinging at a Cocktail Party

Abstract: People often have to listen to someone speak in the presence of competing voices. Much is known about the acoustic cues used to overcome this challenge, but almost nothing is known about the utility of cues derived from experience with particular voices—cues that may be particularly important for older people and others with impaired hearing. Here, we use a version of the coordinate-response-measure procedure to show that people can exploit knowledge of a highly familiar voice (their spouse’s) not only to trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
71
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(88 citation statements)
references
References 19 publications
8
71
0
Order By: Relevance
“…This indexical specificity effect, where linguistic processing is influenced by instance-specific information, has been found across a variety of different tasks, including continuous recognition memory Palmeri et al, 1993), delayed recognition memory (Goh, 2005;Goldinger, 1996;Mattys & Liss, 2008), cued re-call (Church & Schacter, 1994), long-term repetition priming, and lexical decision (González & McLennan, 2007;McLennan & Luce, 2005). Moreover, perceptual experience with a talker's voice characteristics has been found to transfer to enhanced linguistic processing, with higher shadowing or word recognition accuracy for familiar talkers relative to unfamiliar ones (Johnsrude et al, 2013;Newman & Evers, 2007;Nygaard & Pisoni, 1998).…”
Section: Integration Of Linguistic and Signal-intrinsic Non-linguistimentioning
confidence: 99%
See 1 more Smart Citation
“…This indexical specificity effect, where linguistic processing is influenced by instance-specific information, has been found across a variety of different tasks, including continuous recognition memory Palmeri et al, 1993), delayed recognition memory (Goh, 2005;Goldinger, 1996;Mattys & Liss, 2008), cued re-call (Church & Schacter, 1994), long-term repetition priming, and lexical decision (González & McLennan, 2007;McLennan & Luce, 2005). Moreover, perceptual experience with a talker's voice characteristics has been found to transfer to enhanced linguistic processing, with higher shadowing or word recognition accuracy for familiar talkers relative to unfamiliar ones (Johnsrude et al, 2013;Newman & Evers, 2007;Nygaard & Pisoni, 1998).…”
Section: Integration Of Linguistic and Signal-intrinsic Non-linguistimentioning
confidence: 99%
“…A strict version of this notion has been challenged by a burgeoning body of evidence over the past couple of decades demonstrating that linguistic processing is influenced by non-linguistic features of the speech signal, that is, by indexical information, including gender, talker identity, speaking rate, and the speaker's affective state (e.g., Goh, 2005;Goldinger, 1996;Johnsrude et al, 2013;Kaganovich et al, 2006;Mullennix & Pisoni, 1990;Palmeri et al, 1993;Schacter & Church, 1992;Sheffert & Fowler, 1995, and many others). This work has demonstrated that listeners are sensitive to changes in the indexical features of the input, such that listeners were found to be less accurate at identifying or recalling items when the surface characteristics changed from their initial exposure to the items relative to when the surface characteristics remained consistent.…”
Section: Integration Of Linguistic and Signal-intrinsic Non-linguistimentioning
confidence: 99%
“…As shown by Helfer and Freyman (2009), who used a speech perception task similar to the CRM task, results did not depend on whether the target talker could be identified using a key word presented visually, or using an auditory “preview” of the target talker’s voice. Interestingly, Johnsrude et al (2013) recently showed that listeners are much better at suppressing same-sex confusions when the target or interfering talker is highly familiar (the listener’s spouse).…”
Section: Grouping Of Speech Soundsmentioning
confidence: 99%
“…However, age and/or age-related hearing loss appears to reduce the ability to take advantage of these fluctuations (Dubno, Horwitz, & Ahlstrom, 2002George, Festen, & Houtgast, 2006;Summers & Molis, 2004;Takahashi & Bacon, 1992). There is also evidence that older adults are less able to use indexical information, such as the differences between voices (Helfer & Freyman, 2008;Johnsrude et al, 2013; NavehBenjamin & Craik, 1996;Pilotti & Beyer, 2002; RossiKatz & Arehart, 2009;Yonan & Sommers, 2000), which is likely important when trying to identify and attend to one message in the presence of competing talkers.When multiple talkers are present simultaneously in realworld acoustic environments, a particularly salient cue in segregating individual speech streams is the physical point of origin of each voice within that environment (due to the fact that every person occupies his or her own location in space). An essential consideration when examining listening in such competing speech situations is the extent to which the listener can take advantage of spatial separation between the target and masking speech.…”
mentioning
confidence: 99%
“…However, age and/or age-related hearing loss appears to reduce the ability to take advantage of these fluctuations (Dubno, Horwitz, & Ahlstrom, 2002George, Festen, & Houtgast, 2006;Summers & Molis, 2004;Takahashi & Bacon, 1992). There is also evidence that older adults are less able to use indexical information, such as the differences between voices (Helfer & Freyman, 2008;Johnsrude et al, 2013;NavehBenjamin & Craik, 1996;Pilotti & Beyer, 2002;RossiKatz & Arehart, 2009;Yonan & Sommers, 2000), which is likely important when trying to identify and attend to one message in the presence of competing talkers.…”
mentioning
confidence: 99%